Multilayer perceptron approach to condition-based maintenance of marine CODLAG propulsion system components - Lorencin, Ivan; Anđelić, Nikola, inženjer strojarstva; Mrzljak, Vedran; Car, Zlatan, inženjer strojarstva (2019)
In this paper multilayer perceptron (MLP) approach to condition-based maintenance of combined diesel-electric and gas (CODLAG) marine propulsion system is presented. By using data available in UCI, online machine learning repository, MLPs for prediction of gas turbine (GT) and GT compressor decay state coefficients are designed. Aforementioned MLPs are trained and tested by using 11 934 samples, of which 9 548 samples are used for training and 2 386 samples are used testing. In the case of GT decay state coefficient prediction, the lowest mean relative error of 0.622 % is achieved if MLP with one hidden layer of 50 artificial neurons (AN) designed with Tanh activation function is utilized. This configuration achieves the best results if it is trained by using L-BFGS solver. In the case of GT compressor decay state coefficient, the best results are achieved if MLP is designed with four hidden layers of 100, 50, 50 and 20 ANs, respectively. This configuration is designed by using Logistic sigmoid activation function. The lowest mean relative error of 1.094 % is achieved if MLP is trained by using L-BFGS solver.
Bibliografija: 44 jed.
Summary.
Keywords: Brodsko strojarstvo -- Pogonski sustavi -- Umjetna inteligencija -- Višeslojni perceptron